Use of silicon for skin and hair care: an approach of chemical forms available and efficacy - Lidiane Advincula de Araújo; Flavia Addor; Patrícia Maria Berardo Gonçalves Maia Campos (Sociedade Brasileira de Dermatologia, 2016)
Abstract Silicon is the second most abundant element on Earth, and the third most abundant trace element in human body. It is present in water, plant and animal sources. On the skin, it is suggested that silicon is important for optimal collagen synthesis and activation of hydroxylating enzymes, improving skin strength and elasticity. Regarding hair benefits, it was suggested that a higher silicon content in the hair results in a lower rate of hair loss and increased brightness. For these beneficial effects, there is growing interest in scientific studies evaluating the efficacy and safety of using dietary supplements containing silicon. Its use aims at increasing blood levels of this element and improving the skin and its annexes appearance. There are different forms of silicon supplements available and the most important consideration to be made in order to select the best option is related to safety and bioavailability. Silicon supplements are widely used, though there is wide variation in silicon bioavailability, ranging from values below 1% up to values close to 50%, depending on the chemical form. Therefore, the aim of this study was to evaluate the scientific literature related to the different chemical forms of silicon supplements available and the limitations and recent progress in this field. According to reported studies, among the different chemical forms available, the orthosilicic acid (OSA) presents the higher bioavailability, whereas the others forms have absorption inversely proportional to the degree of polymerization. However, clinical studies evaluating safety and efficacy are still lacking.